Nutritional Characterization and Untargeted Metabolomics of Oyster Mushroom Produced Using Astragalus membranaceus var. mongolicus Stems and Leaves as Substrates - Zeng, Xu; Li, Jiaxue; Lyu, Xinkai; Chen, Xiao-Mei; Guo, Shunxing (Frontiers in Plant Science, 2022)
Astragalus membranaceus var. mongolicus (AMM), an edible and medicinal material, is commonly used in East Asia. The dried root of AMM is medicinal. However, the aerial parts of AMM are always directly discarded after harvest. The leaves and stems are also rich in active compounds, including saponins, flavonoids, terpenoids, and polysaccharides. To rationally use resources, waste products from AMM stems and leaves are useful substrates for edible fungus cultivation. Here, oyster mushroom (Pleurotus ostreatus var. florida) was cultivated on a basal substrate supplemented with AMM stems and leaves (AMM group). The nutritional and chemical composition of the fruiting body were analyzed by metabolomics and chemometrics. Our results showed that AMM addition to the substrate affected the fresh weight, moisture, fat, protein and element concentrations, and amino acid composition of oyster mushrooms. Moreover, 2156 metabolites were detected and annotated based on the metabolomics data, of which 680 were identified as differentially expressed metabolites. Many active phytometabolites previously identified in AMM herbs were also detected in the metabolomics of oyster mushroom from AMM group, including 47 terpenoids, 21 flavonoids, 17 alkaloids, 14 phenylpropanoids and 3 fatty acids. In summary, our results imply that oyster mushroom cultured with AMM stems and leaves might have very high nutritional therapy health care value.